What is in it for us? Network effects and bank payment innovation - Milne, Alistair (Journal of Banking & Finance, 2006)
The developed world exhibits substantial but poorly understood differences in the efficiency and quality of low value payment services. This paper compares payment arrangements in the UK, Norway, Sweden, and Finland, and discusses the impact of network effects on incentives to adopt new payments technology. A model is presented, in which private benefits for investment in shared inter-bank payments infrastructure are weak. In contrast, due to ‘account externalities’, there are strong incentives for investment in intra-bank payment systems. These two features, distinguishing bank payments from other network industries, can help explain some of the observed cross-country differences in payment arrangements.